Organic and inorganic hybrid nanofiber membrane prepared by blending electrostatic spinning method and preparation method thereof
By filling in organic materials on the electrospinned fiber membrane and forming a porous structure using enzyme-induced calcium carbonate precipitation technology, the existing electrospinned fiber membranes have been solved, and a nanofiber membrane with high density and strong adsorption performance has been achieved, which is suitable for the dust control field.
Patent Information
- Application Number
- CN202510061733.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-05-02
AI Technical Summary
The existing electrospinned fiber membranes are not effective in suppressing dust, mainly because their internal structure is not dense enough to effectively capture and block dust particles.
By filling the surface, gap or inside of the fiber membrane with inorganic materials, a composite multiphase structure is formed, and the density of the fiber membrane and dust capture ability are improved. Specific methods include blending electrospinning to prepare organic inorganic hybrid nanofiber membranes and generating porous calcium carbonate crystals on the fiber membranes through enzyme-induced calcium carbonate precipitation technology.
It significantly improves the density and adsorption properties of the fiber membrane, enhances the suppression effect on dust, and can maintain efficient dust suppression properties for a long time. At the same time, the process cost is low and environmentally friendly.
Smart Images

Figure CN119913667A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of biotechnology and composite materials, and in particular to a fiber preparation method combining electrostatic spinning with microbial engineering. Background Art
[0002] Electrospinning is a method for preparing polymer fiber materials based on electrohydrodynamics. This technology can combine different materials with matrix fibers to form a new and unique structure with a high surface area ratio, adjustable morphology and diverse composition. The diameter of the fibers produced by electrospinning technology can reach nanometers, and the obtained fiber membrane has the characteristics of large specific surface area and high porosity. In addition, certain properties of the fiber membrane can be changed by changing the electrospinning method such as single needle, multi-needle, coaxial, etc., as well as by using doping, embedding other materials, etc.
[0003] Enzyme-induced calcium carbonate precipitation (EICP) is a technology that uses urease to catalyze the hydrolysis of urea into carbonate ions, which combine with calcium ions to form solid carbonate precipitates. When calcium carbonate crystals fill the pores in the rock and soil matrix, they can change the pore structure characteristics and increase the strength of the soil. It is currently widely used in cultural relics restoration, rock and soil reinforcement, slope protection, and contaminated soil control.
[0004] Although electrospinning technology has significant advantages in preparing nanofiber membranes, the electrospinning fiber membranes currently prepared cannot effectively suppress dust. The main reason is that their internal structure is not dense enough to effectively capture and block dust particles. Dust diffusion not only pollutes the environment, but also poses a threat to human health. Therefore, it is particularly important to develop technologies that can effectively control dust. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defect that the currently prepared electrospun fiber membrane cannot effectively suppress dust. We propose a solution of organic-inorganic hybrid electrospun nanofiber membrane. By filling and coating inorganic materials on the surface, gap or inside of the fiber membrane to form a composite multiphase structure, the density and dust capture ability of the fiber membrane are significantly improved, and the process cost is low. Compared with traditional electrospun membranes, the density of this organic-inorganic hybrid nanofiber membrane is greatly improved, thereby showing higher adsorption performance, and is expected to play an important role in many fields such as catalysis and adsorption, especially showing great application potential in dust control.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] An organic-inorganic hybrid nanofiber membrane prepared by a blended electrostatic spinning method comprises 3wt% to 10wt% of a bonding material, 6wt% to 12wt% of a high molecular polymer, and 78wt% to 91wt% of N,N-dimethylformamide (DMF).
[0008] The high molecular polymer is any one or more of polyacrylonitrile, polyvinyl alcohol, polylactic acid, polyurethane or polystyrene.
[0009] The cementing material is urea and inorganic salt with a concentration of 0.6-1 mol / L, wherein the inorganic salt is any one of anhydrous calcium chloride, calcium acetate or calcium lactate.
[0010] The preparation method is as follows:
[0011] S1, dissolving a high molecular polymer and a binder material in N,N-dimethylformamide, and stirring with a constant temperature magnetic force to obtain a spinning solution rich in the polymer and the binder material;
[0012] S2, adding the spinning solution into the electrospinning device to obtain a nanofiber membrane; the thickness of the nanofiber membrane is about 300 μm, such as 300 μm ± 50 μm; the preferred electrospinning parameters are: voltage of 15 kV-30 kV, distance from nozzle tip to collector of 10-20 cm, solution flow rate of 0.4 mL / h, injection speed of 0.01-0.04 mL / min, and needle size of 1.0-1.6 mm;
[0013] S3. Cut the nanofiber membrane and soak it in a urease solution; urea produces carbonate under urease metabolism, and calcium ions and carbonates form porous calcium carbonate crystals on the nanofiber membrane. After the reaction is completed, the unbound carbonate crystals are rinsed with deionized water and dried to obtain the product. Preferably, the urease used in the urease solution is crudely extracted soybean urease, which is obtained by roasting, crushing, filtering, stirring and centrifuging soybeans. Furthermore, the urease activity is about 10.5-21.9mmol / (L·min) at 25°C.
[0014] Urease decomposes urea to produce carbonate ions, which co-precipitate with calcium ions to form calcium carbonate crystals on the surface of the interlaced polymer fiber filaments. The nanofiber membrane filled with a large amount of calcium carbonate particles not only improves the shortcomings of traditional electrospun nanofibers such as poor mechanical properties and lack of surface specificity, but also has higher density and better environmental adaptability, and has a good dust suppression effect.
[0015] The beneficial effects achieved by the present invention are as follows: the present invention combines the high specific surface area and strong binding ability of the electrospun fiber membrane with the calcium carbonate precipitation generated by the EICP technology, and the nano-scale polymer fibers provide numerous nucleation sites for the generation of calcium carbonate, which not only fills the gaps on the original fiber membrane but also significantly improves the adsorption capacity and density of the electrospun fiber membrane; at the same time, the calcium carbonate generated by EICP has good stability, and the structure formed after combining with the polymer fiber membrane is not easily damaged, and can maintain a high-efficiency dust suppression effect for a long time.
[0016] The factors affecting the pore size of nanofiber membranes are mainly the viscosity of the spinning solution and the process parameters during spinning. The viscosity of the spinning solution can be changed by the proportion of raw materials added, mainly the proportion of organic polymers; the process parameters during spinning such as voltage, receiving distance, needle size, etc. will affect the thickness of the membrane. The principle of fiber membrane forming is that the filaments ejected by the equipment are continuously received and stacked by the receiving cloth below, so when the stacking reaches the ideal thickness, the fiber membrane can be removed from the receiving cloth. Of course, the way to achieve the ideal thickness can be one-time forming or the superposition of different small thicknesses. Therefore, the thickness of the membrane can be adjusted according to specific needs.
[0017] Electrospinning technology has low energy consumption and low pollution, does not involve high temperature or harmful chemical reactions, and the production process has little negative impact on the environment. EICP technology itself is an environmentally friendly technology, and the calcium carbonate generated is also a common substance in the environment, non-toxic and harmless, and will not release harmful gases or pollute the environment during application. The product has strong overall stability during application, and the substance rarely escapes from the environment again before and after use, and its stability prevents it from releasing harmful substances during its service life. Therefore, the nanofiber membrane of the present invention is an environmentally friendly high-density nanofiber membrane.
[0018] The obtained nanofiber membrane is an environmentally friendly, high-density nanofiber membrane that has a strong adsorption capacity for dust and suppresses the diffusion of dust through its dense internal structure. Spinning is done by electrostatic electron beam, and the obtained fiber membrane is a nano-level material with an extremely high specific surface area. The process is green and environmentally friendly with low cost. The obtained nanofiber membrane can be widely used in construction sites, mines, material yards and other environments. The thickness and pore size of the membrane can be adjusted according to specific needs to adapt to different dust control scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 : SEM image (50 μm) of the organic and inorganic hybrid nanofiber membrane obtained in Example 6;
[0020] Figure 2 : SEM image (20 μm) of the organic and inorganic hybrid nanofiber membrane obtained in Example 6;
[0021] Figure 3 : SEM image of the polymer fiber membrane obtained in the comparative example;
[0022] Figure 4 : Comparison of long-term dust suppression rate between Example 6 and the comparative example. DETAILED DESCRIPTION
[0023] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0024] Example 1
[0025] The nanofiber membrane was prepared as follows:
[0026] (1) A high molecular weight polymer and 1.8 g of urea and an inorganic salt with a concentration of 0.6 mol / L were dissolved in 50 ml of an organic solvent, N,N-dimethylformamide, to obtain a mixed solution. The mixed solution was magnetically stirred at a constant temperature for 30 min to obtain a spinning solution, which was spun into a nanofiber membrane with a thickness of 300 μm using electrospinning technology; the high molecular weight polymer was 3.19 g of polyacrylonitrile PAN, and the inorganic salt was 3.3 g of anhydrous calcium chloride; the voltage of electrospinning was 15-30 kV, the distance from the spinning nozzle to the receiver was 15-20 cm, the solution flow rate was 0.4 mL / h, the injection speed was 0.01-0.04 mL / min, and the needle size was 1.0-1.6 mm.
[0027] (2) Cut the nanofiber membrane obtained in step (1) into square nanofiber membranes with a side length of 20×20 cm.
[0028] (3) The square nanofiber membrane was immersed in a 50 mL aqueous solution containing urease for 30 min, and the urease activity was maintained at 18-20 mmol / (L·min). Urea was metabolized by urease to produce carbonate, and calcium ions and carbonate formed porous calcium carbonate crystals on the nanofiber membrane. After the reaction was completed, the unbound carbonate crystals were rinsed with deionized water and dried to obtain the organic-inorganic hybrid nanofiber membrane prepared by the blended electrospinning method.
[0029] Example 2
[0030] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.19 g of polyvinyl alcohol (PVA).
[0031] Example 3
[0032] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.2 g of polylactic acid PLA.
[0033] Example 4
[0034] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.2 g of polyurethane PU.
[0035] Example 5
[0036] The difference between this embodiment and embodiment 1 is that the polymer used is 3.2g polystyrene PS
[0037] Example 6
[0038] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 4.94g polyacrylonitrile PAN
[0039] Example 7
[0040] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 4.94g polyvinyl alcohol PVA
[0041] Example 8
[0042] The difference between this embodiment and embodiment 1 is that the polymer used is 4.94g polystyrene PS
[0043] Example 9
[0044] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 6.81g polyacrylonitrile PAN
[0045] Example 10
[0046] The difference between this embodiment and embodiment 1 is that the polymer used is 6.81g polystyrene PS
[0047] Embodiment 11
[0048] The difference between this embodiment and embodiment 1 is that the inorganic salt used is 6.3 g of calcium acetate.
[0049] Example 12
[0050] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.19 g of polyvinyl alcohol; and the inorganic salt used is 6.3 g of calcium acetate.
[0051] Example 13
[0052] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.2 g of polystyrene; and the inorganic salt used is 6.3 g of calcium acetate.
[0053] Embodiment 14
[0054] The difference between this embodiment and embodiment 1 is that the inorganic salt used is 6.56 g of calcium nitrate.
[0055] Embodiment 15
[0056] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.19 g of polyvinyl alcohol; and the inorganic salt used is 6.56 gg of calcium nitrate.
[0057] Example 16
[0058] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 3.2 g of polystyrene; and the inorganic salt used is 6.56 g of calcium nitrate.
[0059] Embodiment 17
[0060] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 4.9 g of polyacrylonitrile, and the concentrations of the binder materials urea and anhydrous calcium chloride are 0.8 mol / L, which are 2.4 g and 4.3 g respectively.
[0061] Embodiment 18
[0062] The difference between this embodiment and embodiment 17 is that the high molecular polymer used is 4.9 g of polyvinyl alcohol.
[0063] Embodiment 19
[0064] The difference between this embodiment and embodiment 17 is that the high molecular polymer used is 4.9 g of polystyrene.
[0065] Embodiment 20
[0066] The difference between this embodiment and embodiment 1 is that the high molecular polymer used is 4.9 g of polyacrylonitrile, and the concentrations of the binder materials urea and anhydrous calcium chloride are 1 mol / L, 3 g and 5.5 g respectively.
[0067] Embodiment 21
[0068] The difference between this embodiment and embodiment 20 is that the high molecular polymer used is 4.9g polystyrene.
[0069] The preparation method of the comparative example was the same as steps (1) and (2) of Example 6, and only a square nanofiber membrane was obtained without modification.
[0070] Performance Test:
[0071] The fiber membranes obtained in Examples 1-21 of the present invention and the comparative example were subjected to relevant performance tests:
[0072] Dust control testing:
[0073] Dust suppression rate: Use wind-blown sand erosion equipment to measure the amount of dust loss before and after covering, and test its ability to control dust diffusion based on the classification and technical requirements of exhaust hoods in GB / T16758-2008.
[0074] The specific experimental steps for dust suppression rate test are as follows:
[0075] Prepare sand table samples, dust, and wind erosion equipment. The sand table sample uses a square iron plate with a size of 20cm×10cm×3cm (length×width×height), and the particle size of the dust is between 3-10μm.
[0076] The present invention conducts an indoor dust suppression test by placing a nanofiber composite membrane sample and a polymer nanofiber membrane in a self-made wind tunnel device. The fiber membrane is covered on a square iron plate filled with dust, and the test is started after weighing. The wind speed is set to 10-15m / s to simulate the wind erosion environment, and the test time is 20 minutes. After the test is completed, the remaining mass of the sand table is weighed and compared with the initial mass to obtain the dust suppression rate and long-term dust suppression rate, so as to evaluate the dust suppression rate of different membrane materials.
[0077] In order to evaluate the long-term dust suppression effect of membrane materials, the nanofiber composite membrane samples and polymer nanofiber membranes were placed in a homemade wind tunnel device for a 7-day erosion test. Wind erosion was carried out for 8 hours a day, and the wind speed was set to 10m / s. After the test each day, the remaining mass of the sand table was weighed and compared with the original mass to obtain the daily dust suppression rate. This change was used to evaluate the long-term dust suppression rate of the fiber membrane.
[0078] Air permeability and porosity testing:
[0079] The air permeability and pore size of the covering material affect its ability to control dust. The test is carried out in accordance with GB / T5453-1997.
[0080] The fiber membranes obtained in Examples 1-21 and Comparative Example were subjected to an air permeability resistance test to determine the air permeability.
[0081] The specific experimental steps are as follows:
[0082] The fiber membranes obtained in Examples 1-21 of the present invention and the comparative example were subjected to air resistance test, with a gas flow rate of 85 L / min. The samples were placed in a fully automatic air permeability tester to measure the air permeability of the samples. The test method was set to the pressure difference method, the pressure drop value was set to 100 Pa, the orifice diameter was 4.5 mm, and the test area was 20 cm 2 .
[0083] The porosity test was performed on the fiber membranes obtained in Examples 1-21 and Comparative Examples:
[0084] The specific experimental steps are as follows:
[0085] The fiber membrane was cut into square samples with a side length of 20 cm, and the fiber membrane to be tested was placed in a glass bottle filled with dust. The fiber membrane before and after being placed in the glass bottle was tested using a high-speed automatic specific surface and porosity analyzer to measure the specific surface area and pore volume of the fiber membrane. The analysis gas was nitrogen, the analysis tank temperature was 77.3K, the sample thickness was 100μm, and the equilibrium time interval was 5s.
[0086] The specific test results are shown in Table 1:
[0087] Table 1: Test results of various embodiments
[0088]
[0089]
[0090] It can be seen from the test results in Table 1 that Examples 1-5 were tested using different types of polymers with a mass fraction of 6wt%. The results show that the dust suppression rates of Examples 1 and 5 were both above 50%, while the air permeability and porosity were also maintained at a good level in comparison. The test data of Examples 2 and 4 show that the polymers of the two are relatively similar. Considering the raw material cost and applicability issues, the polymer selected in Example 2 is given priority.
[0091] Examples 6-8 were tested by increasing the mass fraction of the preferred high molecular polymer in the solution to 9wt%. The test results of Examples 6 and 8 were the most ideal, with the dust suppression rate reaching more than 75%, and the air permeability being able to suppress the diffusion of dust with a particle size of ≤10μm. At the same time, the preferred polymers (polyacrylonitrile and polystyrene) have the advantages of stable fiber structure, high fiber strength, durability, non-degradability, easy material acquisition, and low cost compared to other polymers. Therefore, considering the physical and chemical properties and economic benefits, the nanofiber membrane using the organic polymer polyacrylonitrile with a mass fraction of 9wt% can exert the most ideal dust suppression effect.
[0092] Examples 9 and 10 studied the test effect when the mass fraction of the organic polymer was increased to 12%. Although the dust suppression rate reached more than 50%, the electrospinning process was very difficult due to the excessive viscosity of the spinning solution. Therefore, considering the difficulty and effect of the test, the mass fraction of the organic polymer was no longer increased, and a mass fraction of 9wt% was selected as the optimal organic polymer dosage.
[0093] Examples 11-16 explore the influence of different inorganic salt materials on the dust suppression effect. Compared with the test results of Examples 1, 2 and 5, the dust suppression rates did not reach 50%. This shows that anhydrous calcium chloride can better play the role of EICP technology as a calcium source for urease and achieve more calcium carbonate precipitation. Therefore, anhydrous calcium chloride is used as the optimal inorganic salt material.
[0094] Examples 17-21 explored the effect of binder concentrations of 0.8 and 1 mol / L on dust suppression. High concentrations of additives resulted in excessive viscosity of the solution, needle blockage during the electrospinning process, solution coagulation, and other problems. The fiber membrane was not easy to form, resulting in unsatisfactory test results. Therefore, the optimal binder concentration is 0.6 mol / L.
[0095] By comparing Examples 1-21 with the control examples that were not treated with the EICP technology, the dust suppression capabilities of the samples treated with the EICP technology were improved to varying degrees, with the highest dust suppression rate increased by 56.2%, the highest air permeability reduced by 60.1%, and the highest porosity reduced by 54.2%. As the polymer concentration increases appropriately, the dust suppression ability of the sample is improved; at the same time, different binder materials and concentrations affect the dust suppression ability of the sample to a certain extent. The dust blocking effect of the sample is related to the air permeability. The smaller the air permeability, the better the dust blocking effect of the fiber membrane. Porosity refers to the percentage of pore volume to the total volume of the carrier. A lower porosity means that the fiber membrane is more effective in blocking dust.
[0096] By comparing the long-term dust suppression rate of Example 6 with that of the comparative example not treated with the EICP technology, Figure 4 It can be seen that the dust suppression rates of both decreased over time, but the decrease rate of Example 6 was relatively slow. However, the dust suppression effect of Example 6 was significantly better than that of the comparative example, and a high dust suppression rate was maintained throughout the observation period. The dust suppression rates of Example 6 and the comparative example on the 7th day were 41.1% and 9.4%, respectively, and the dust suppression rate increased by 31.7%. The long-term dust suppression rate evaluates the change of its dust suppression effect over time. The higher the long-term dust suppression rate, the better the long-term stability of the fiber membrane in blocking dust.
[0097] from Figure 1 and Figure 2 It can be seen that the fiber membrane obtained by the present invention is a nano-level material and has an extremely high specific surface area. The nano-level fine fibers greatly increase the contact area per unit area. The specific surface area refers to the surface area per unit mass or volume. The smaller the fiber diameter, the larger the surface area contained in the unit mass or volume. At the same time, the three-dimensional network structure formed by the cross-linking of the fibers can provide more surface positions. By adjusting parameters such as the electric field strength, solution concentration, and the distance between the nozzle and the receiving cloth, the diameter of the fiber can be controlled and even made adjustable at the nanometer level.
[0098] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. The organic and inorganic hybrid nanofiber membranes are prepared by a blended electrospinning method, characterized in that: The invention comprises 3wt% to 10wt% of a bonding material, 6wt% to 12wt% of a high molecular polymer and 78wt% to 91wt% of N,N-dimethylformamide.
2. The method for preparing organic and inorganic hybrid nanofiber membranes by using a blended electrospinning method as claimed in claim 1, characterized in that: The high molecular polymer is any one or more of polyacrylonitrile, polyvinyl alcohol, polylactic acid, polyurethane or polystyrene.
3. The method for preparing organic and inorganic hybrid nanofiber membranes by using a blended electrospinning method as claimed in claim 1, characterized in that: The cementing material comprises urea and inorganic salts with a concentration of 0.6-1 mol / L, wherein the inorganic salt is any one of anhydrous calcium chloride, calcium acetate or calcium lactate.
4. The method for preparing organic and inorganic hybrid nanofiber membranes by using a blended electrospinning method as claimed in claim 1, characterized in that: The following steps are involved: S1, dissolving a high molecular polymer and a binder material in N,N-dimethylformamide to obtain a spinning solution rich in the polymer and the binder material; S2, adding the spinning solution into the electrospinning device to obtain the nanofiber membrane; S3, cutting the nanofiber membrane and immersing it in a urease solution for reaction; after the reaction is completed, rinsing and drying, the nanofiber membrane is obtained.
5. The preparation method according to claim 4, characterized in that: The thickness of the nanofiber membrane obtained by S2 is 300μm±50μm.
6. The preparation method according to claim 4, characterized in that: The electrospinning parameters in S2 were: voltage of 15 kV-30 kV, distance from nozzle tip to collector of 10-20 cm, solution flow rate of 0.4 mL / h, injection speed of 0.01-0.04 mL / min, and needle size of 1.0-1.6 mm.
7. The preparation method according to claim 4, characterized in that: The urease used in the urease solution in S3 is crudely extracted soybean urease, which is obtained by roasting, crushing, filtering, stirring and centrifuging soybeans.
8. The preparation method according to claim 7, characterized in that: The urease activity was 10.5-21.9 mmol / (L·min) at 25℃.
9. The preparation method according to claim 7, characterized in that: 4.94 g of polyvinyl alcohol, 1.8 g of urea with a concentration of 0.6 mol / L, and 3.3 g of anhydrous calcium chloride were dissolved in 50 ml of an organic solvent, N,N-dimethylformamide, to obtain a mixed solution, the mixed solution was stirred to obtain a spinning solution, and the solution was spun into a nanofiber membrane with a thickness of 300 μm using an electrospinning technique; the voltage of the electrospinning was 15-30 kV, the distance from the spinning nozzle to the receiver was 15-20 cm, the solution flow rate was 0.4 mL / h, the injection speed was 0.01-0.04 mL / min, and the needle size was 1.0-1.6 mm; The nanofiber membrane is placed in 50 mL of an aqueous solution containing urease for reaction, and the urease activity is maintained at 18-20 mmol / (L·min). After the reaction is completed, the membrane is rinsed and dried to obtain the membrane.
Citation Information
Patent Citations
Calcium chloride cross-linked sodium alginate nanometer fiber scaffold material and preparation method thereof
CN105457094A
Preparation method of needling filter material
CN108404521A
Preparation method of calcium carbonate / polymer nanofiber composite membrane
CN113914094A
Improved soybean urease extraction method applied to EICP (Enhanced Inductively Coupled Plasma) technology
CN118028273A